More heat, less sag [power cable upgrades]. - Jones, W.D.
This paper reports on the development of new high voltage cables that don't sag nearly as much as the power lines they would replace. By replacing the steel core that gives the cable its strength with novel composite materials, heat is reduced thereby minimizing sagging. One such low-sag, composite core transmission cable has been developed by the CA-based Composite Technology Corp. (CTC). Called aluminum composite conductor core (ACCC), the strength and resilience of these new cables are derived from fiberglass-encased carbon fiber. In addition to less sag, ACCC have more current carrying capacity than a typical cable with the same overall thickness. A similar low-sag cable, called aluminum conductor composite reinforced (ACCR) cable, has also been developed by 3M Co. except that it is made from a matrix of aluminum oxide fibers embedded in pure aluminum surrounded by wires made of hardened aluminum doped with zirconium for strength. Although these new cables are more expensive than steel-core cables, the economics of using them are attractive because of their greater current carrying capacity
Keywords: Composite Technology Corp; Aluminium oxide fibers; Aluminum composite conductor core; Aluminum conductor composite reinforced cable; Composite cores; Current-carrying capacity; High-voltage power cable; Overhead cable sagging; Power blackouts; Power cable upgrades; Power delivery improvements